Rancang Bangun Game Edukasi Siklus Air untuk Media Pembelajaran Siswa Kelas 5 SD - Ariqoh, Reky; Nurkifli, E. Haodudin; Yusup, Dadang Haodudin (Jurnal Ilmiah Wahana Pendidikan, 2026)
Elementary school students' understanding of the water cycle is often hampered by its abstract nature. This study aims to develop an educational game with a water cycle theme using the Multimedia Development Life Cycle (MDLC) method as an interactive learning medium. The game was developed using GDevelop 5 and tested through alpha testing (by media and material experts) and beta testing (by 5th grade students of SDN 1 Trusmi Kulon). The feasibility test results showed that the game was categorized as very feasible with a feasibility score of 100% from media experts, 80% from material experts, and 93.62% from users. The effectiveness test with N-Gain showed an increase in student understanding with an average score of 56%, which is included in the fairly effective category. These results indicate that the designed educational game effectively supports the science learning process in elementary schools.